From apartheid to empire: How (post)apartheid South Africa became an anti-poor black society - Zuma, Buhle (PINS-Psychology in Society, 2021)
Using psycho-political analysis as a method of seeing and interpreting, this essay meditates on why and how Frantz Fanon’s observation that ‘the Black is not a [hu]man’ is true in (post)apartheid South Africa. In particular, the essay is concerned with the histo-political circumstances that make Fanon’s observation true for poor black people. And to this end, the essay argues that local and international white-monopoly capital orchestrated a psycho-political defeat and co-option of the ANC well ahead of the 1994 democratic elections. Consequently, South Africa transitioned from apartheid into recolonisation as a satellite of the empire of capital thus, closing all prospects of a decent and dignified life for poor black people. Using a newspaper article as an illustrative example, the essay analyses the lived experience of poor black people as a consequence of the ANC’s psycho-political defeat and custodianship of capital imperialism in South Africa. In this, the essay shows the violence of the ANC government on poor black people and the fate of the latter as a disposable population of the empire of capital.